Temperature Control in Acute Brain Injury: An Update - Lin, Victor; Tian, Cindy; Wahlster, Sarah; Castillo-Pinto, Carlos; Mainali, Shraddha; Johnson, Nicholas J. (Seminars in Neurology, 2024)
Temperature control in severe acute brain injury (SABI) is a key component of acute management. This manuscript delves into the complex role of temperature management in SABI, encompassing conditions like traumatic brain injury (TBI), acute ischemic stroke (AIS), intracerebral hemorrhage (ICH), aneurysmal subarachnoid hemorrhage (aSAH), and hypoxemic/ischemic brain injury following cardiac arrest. Fever is a common complication in SABI and is linked to worse neurological outcomes due to increased inflammatory responses and intracranial pressure (ICP). Temperature management, particularly hypothermic temperature control (HTC), appears to mitigate these adverse effects primarily by reducing cerebral metabolic demand and dampening inflammatory pathways. However, the effectiveness of HTC varies across different SABI conditions. In the context of post-cardiac arrest, the impact of HTC on neurological outcomes has shown inconsistent results. In cases of TBI, HTC seems promising for reducing ICP, but its influence on long-term outcomes remains uncertain. For AIS, clinical trials have yet to conclusively demonstrate the benefits of HTC, despite encouraging preclinical evidence. This variability in efficacy is also observed in ICH, aSAH, bacterial meningitis, and status epilepticus. In pediatric and neonatal populations, while HTC shows significant benefits in hypoxic-ischemic encephalopathy, its effectiveness in other brain injuries is mixed. Although the theoretical basis for employing temperature control, especially HTC, is strong, the clinical outcomes differ among various SABI subtypes. The current consensus indicates that fever prevention is beneficial across the board, but the application and effectiveness of HTC are more nuanced, underscoring the need for further research to establish optimal temperature management strategies. Here we provide an overview of the clinical evidence surrounding the use of temperature control in various types of SABI.
Keywords: temperature; severe acute brain injury; hypothermia; cooling; targeted temperature management; TTM; cardiac arrest; traumatic brain injury